2006
DOI: 10.1002/app.24836
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of composites of polyethylene or maleated polyethylene and cellulose or cellulose esters

Abstract: Composites of linear low-density poly(ethylene-co-butene) (PE) or maleated linear low-density poly (ethylene-co-butene) (M-PE) and cellulose (CEL), cellulose acetate (CA), cellulose acetate propionate (CAP), or cellulose acetate butyrate (CAB) were prepared in an internal laboratory mixer with 20 wt % polysaccharide. The structure and properties of the composites were studied with tensile testing, dynamic mechanical thermal analysis, differential scanning calorimetry, extraction with a selective solvent, Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
2
23
0
1
Order By: Relevance
“…Natural polymer shows however some limitations, for instance with regard to poor processability or high water absorbency. Cellulose esters such as cellulose acetate (CA), cellulose acetate propionate (CAP) and cellulose acetate butyrate (CAB) are less hydrophilic than cellulose, thermoplastic materials [4]. To improve their processability and mechanical properties, the addition of plasticizers is usable.…”
Section: Introductionmentioning
confidence: 99%
“…Natural polymer shows however some limitations, for instance with regard to poor processability or high water absorbency. Cellulose esters such as cellulose acetate (CA), cellulose acetate propionate (CAP) and cellulose acetate butyrate (CAB) are less hydrophilic than cellulose, thermoplastic materials [4]. To improve their processability and mechanical properties, the addition of plasticizers is usable.…”
Section: Introductionmentioning
confidence: 99%
“…HDPE was from scrapped milk bottles originally manufactured with Paxon AD60-007 (ExxonChemical, Houston, TX) with a melt index of 0.7 g/10 min and a density of 0.960 g/cm 3 . Both agave fibers and HDPE were washed, dried, and milled before processing.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Metal uptake studies were conducted in a pH range at which most industrial effluents are discharged. 24 The pH was adjusted with NaOH or HNO 3 . We carried out the adsorption experiments in 15-mL glass vials by contacting [2 h for Cu(II) and 24 h for Cd(II)] about 1 g of CCC with 10 mL each of metal solution in a reciprocal Barnstead Shke5000-7 shaker bed at 298 K (West Chester, PA).…”
Section: Equilibrium Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous papers, starch/PEcomposites [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], lignin/PE [21][22][23][24], husk/PE [25][26][27], cellulose/PE [28][29][30][31][32], and wood flour/PE [33][34] showed that all of the biomass were being interest for research.Preparation of biodegradable films by acetylated acid modified rice starches and the thermal properties have been extensively studied [35].Thermoplastic starch could be an ideal matrix for packaging material or single-use articles, because it is a renewable resource material and biodegradable [36]. Since water is a plasticizer for starch, the performance of thermoplastic starch may be unstable and depending on the moisture contents, being in equilibrium with the ambient relative humidity [37].…”
Section: Introductionmentioning
confidence: 99%